Pharmacists’ Knowledge, Attitudes and Practices Regarding Drug Substitution in Pharmacies in the City of Yaounde - Minyem , AP; Soppo, CV; Pekoulef , M; Mbole , JM; Nyangono , M; Nko’o, MHJ; Maniepi , SJ; Aba’a, DM; Ngolsou , F; Ndzie , BP; Benga , FC; Obono , P; et al. (HEALTH SCIENCES AND DISEASE, 2024)
RÉSUMÉ Introduction. La substitution permet aux patients d’avoir accès aux médicaments. Plusieurs pays ont développé la substitution médicamenteuse pour une meilleure prise en charge des malades. Cependant, le manque de connaissances, attitudes et pratiques des pharmaciens d’officine limiterait la substitution pendant la dispensation. L’objectif de ce travail était d’évaluer les connaissances, les attitudes et les pratiques des pharmaciens d’officine à Yaoundé. Méthodologie. Une étude descriptive transversale a été menée auprès des pharmaciens d’officine de Yaoundé. Un questionnaire leur a été envoyé via Google form pendant 07 mois. L’échantillonnage était consécutif non probabiliste. Résultats. Sur 173 pharmaciens d’officine contactés, 73 ont rempli le questionnaire. 82,2% des participants étaient au courant de l’existence d’un texte règlementaire sur la substitution médicamenteuse au Cameroun. La substitution par des génériques et les bio-similaires est reconnue par la Loi selon 60,3% des répondants. 80,8% des participants savaient définir la substitution des médicaments et plus de 60,0% des participants ne savaient pas définir les bio-similaires. 70,5% ont une attitude juste sur la substitution des médicaments. Le pourcentage global des pratiques des pharmaciens était de 54,3%. Conclusion. Cette étude a révélé que les pharmaciens manquaient de connaissances sur la substitution des médicaments. Un grand nombre avait une attitude juste et plus de la moitié avait une pratique insuffisante. La réticence des médecins et des patients était un facteur limitant de la pratique de substitution selon la majorité des pharmaciens. ABSTRACT Background. Substitution is used to give patients access to medicines. To improve patient care, several countries have developed a policy of drug substitution. However, the lack of knowledge, attitudes, and practices of pharmacists may limit the practice of substitution during dispensing. The aim of this study was therefore to assess the knowledge, attitudes, and practices of dispensing pharmacists in the city of Yaoundé. Methods. A cross-sectional descriptive study was conducted among dispensing pharmacists in Yaoundé. A 23-question questionnaire was sent to pharmacists using Google Forms over 7 months. The target population consisted of dispensing pharmacists in Yaoundé. Sampling was consecutive and non-probabilistic. Results. Of the 173 dispensing pharmacists contacted, 73 completed the questionnaire. 82.2% of participants were aware of the existence of a regulatory text on drug substitution in Cameroon. Substitution by generics and biosimilars is recognised by law according to 60.3% of respondents. 80.8% of participants knew how to define drug substitution and more than 60.0% of participants did not know biosimilar definition. 70.5% had the right attitude to drug substitution. 94.5% practiced substitution, while 73.6% did not consult the prescriber before substitution. The overall percentage of pharmacists’ practices was 54.3%. Conclusion. This study revealed that pharmacists lacked knowledge about drug substitution. Conversely, a large number had the right attitude and more than half had insufficient practice. The reluctance of doctors and patients was a factor limiting substitution practice according to the majority of pharmacists.